Ultrasonic inspection of near surface defects with additive manufactured metasurface lens - Zhu, Qi; Zhang, Yuanjun; Zhang, Haiyan; Memoli, Gianluca (Frontiers in Materials, 2022)
Acoustic metasurfaces have been increasingly explored in the past 10 years because of their compact structure and wave manipulation capabilities. In this work, we explore the feasibility of using an acoustic metasurface lens (MSL) for the characterization of near surface defects in NDT. First, we delimited the design space for a MSL operating at 100 kHz, in terms of spatial footprint and materials, and then realized a library of labyrinthine cells optimized for transmission. Then, we assembled the unit cells into lens and simulated its performance in a hole inspection process. The time-domain simulations predicted an increase in scattering and interface effects but, thanks to the focusing behavior, they also showed a much lower drop in the peak amplitude (20%, compared to 70% without MSL). Finally, we validated the simulations using a UTR9000-based MSL on an acrylic sample. Experiments with the MSL showed a converging energy profile, reduced to half of its width without the lens, and the presence of additional transmission peaks allowed to determine the defect diameter with excellent precision, thus circumventing near surface interference. Our study may be the first step towards flexible beam control systems based on a single transducer.